Monthly Breast Exam Pada Remaja Sebagai Upaya Deteksi Dini Kanker Payudara: Monthly Breast Exam Pada Remaja Sebagai Upaya Deteksi Dini Kanker Payudara - Hikmanti, Arlyana; Feti Kumala Dewi; Linda Yanti; Susilo Rini (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
Breast cancer is a malignancy that often occurs in women, especially in women who have menstruated, including teenagers. However, these women often misunderstand the benefits of breast cancer screening programs such as Awareness examinations, clinical examinations and mammography examinations. The health problem faced at SMA Negeri 1 Rancah Ciamis, West Java is that teenagers do not know about the Monthly Breast Self Exam or are aware of it. The methods used in this PkM include preparation, socialization of the importance of solutions, participant screening, implementation of activities, monitoring and evaluation. This science and technology implementation program aims to: 1). Improving teenagers' skills in carrying out Monthly Breast Self Exam/awareness examinations to detect breast cancer early. 2). Awareness examination was carried out by teenagers to detect breast cancer early at SMA Negeri 1 Rancah Ciamis, West Java. The results of this activity are 1). Adolescents are skilled in carrying out Monthly Breast Self Exams/be aware to detect breast cancer early; 2). Monthly Breast Self Exam/be aware by teenagers for early detection. Keywords: early detection, monthly breast exam, teenagers